Inflation targeting strategies in small open economies - Kai Leitemo (University of Oslo, Department of Economics, 1999)
According to recent literature on monetary policy, there are two different interpretations of inflation targeting; (1) an instrument rule that responds to a measure of inflation (forecast) deviations from target and (2) a discretionary optimizing strategy towards minimizing the inflation deviations from its target. This paper compares these strategies with some simple rules for monetary policy. In particular, attention is given to the strategies' impact on the traded and non-traded sectors of the economy. Our conclusions suggest that there are considerable advantages in committing to a specific interest rate rule instead of letting the central bank discretionarily decide on the inflation targeting policy. The paper also provides evidence that the Taylor rule may work reasonably well in an open economy setting and gives only partial support for the Ball (1998) critique. It also discusses the structural conditions for successful targeting of inflation.
Keywords: 330; monetary policy; inflation targeting; simple rules; small open economy; Inflation Targeting; Geldpolitik; Kleines-offenes-Land; Theorie